PERLINDUNGAN HUKUM TEHADAP LAHAN TERBUKA HIJAU YANG BERALIH FUNGSI AKIBAT PENERAPA SISTEM SINGLE SUBMISSION (OSS) DI DESA PERRENAN BADUNG - Bidiawati, Ni Wayan; Permadhi, Putu Lantika Oka (Jurnal Hukum Mahasiswa, 2024)
Green open space is an elongated area/path and/or cluster, whose use is more open, where plants grow, both those that grow naturally and those that are deliberately planted. As regulated in Article 1 number 31 of Law Number 26 of 2007 concerning Spatial Planning (UUPR), however, in Pererenan Village, many green open areas such as rice fields have been converted into buildings due to the implementation of the online single submission system. From the background above, the author will discuss about regulation of the implementation of OSS system permits and legal protection for green open land that has changed its function in Pererenan Badung Village. This research uses empirical legal research methods with a sociological approach. The data used are primary data, secondary data, and tertiary data which were collected using document study techniques, interview techniques, and observation techniques which were then analyzed using qualitative data analysis and then the research results were presented descriptively. The results of this research are in the setting of permit implementation OSS and legal protection seen from 3 (three) elements of action, namely pre-emptive, preventive and repressive.